2010
DOI: 10.1364/ao.49.003713
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving radius, concentration, optical depth, and mass of different types of aerosols from high-resolution infrared nadir spectra

Abstract: We present a sophisticated radiative transfer code for modeling outgoing IR radiation from planetary atmospheres and, conversely, for retrieving atmospheric properties from high-resolution nadir-observed spectra. The forward model is built around a doubling-adding routine and calculates, in a spherical refractive geometry, the outgoing radiation emitted by the Earth and the atmosphere containing one layer of aerosol. The inverse model uses an optimal estimation approach and can simultaneously retrieve atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 67 publications
1
108
0
Order By: Relevance
“…Observational constraints on volcanic ash emissions were provided through infrared satellite retrievals of total column airborne ash loadings (Prata, 1989;Prata and Grant, 2001;Clarisse et al, 2010a) using data from two different satellite instruments, the geosynchronous Meteosat Second Generation (MSG) Spin-stabilised Enhanced Visible and Infrared Imager (SEVIRI) and the polar-orbiting MetOp Infrared Atmospheric Sounding Interferometer (IASI). These two instruments combine high temporal coverage (SEVIRI has a sampling time of 15 min but hourly averages were used here), with an enhanced sensitivity to ash (IASI has over 1000 spectral channels which can be used for ash detection).…”
Section: Satellite Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Observational constraints on volcanic ash emissions were provided through infrared satellite retrievals of total column airborne ash loadings (Prata, 1989;Prata and Grant, 2001;Clarisse et al, 2010a) using data from two different satellite instruments, the geosynchronous Meteosat Second Generation (MSG) Spin-stabilised Enhanced Visible and Infrared Imager (SEVIRI) and the polar-orbiting MetOp Infrared Atmospheric Sounding Interferometer (IASI). These two instruments combine high temporal coverage (SEVIRI has a sampling time of 15 min but hourly averages were used here), with an enhanced sensitivity to ash (IASI has over 1000 spectral channels which can be used for ash detection).…”
Section: Satellite Datamentioning
confidence: 99%
“…Infrared sounding of aerosols has, however, a number of distinct advantages, such as the availability of night time data and the high sensitivity to aerosol morphology. Due to its complexity, a sophisticated method for retrieving radius and mass loadings (Clarisse et al, 2010a), based on optimal estimation which iteratively fits synthetic spectra to an observed spectrum by varying radius and mass loading is not suitable for the treatment of large amounts of data. Another difficulty is that reliable results can only be obtained if the wavenumber-resolved refractive index of the observed aerosols is known.…”
Section: Iasimentioning
confidence: 99%
“…Barton et al, 1992;Wen and Rose, 1994;Prata and Grant, 2001) and its limitations and challenges are discussed by Simpson et al (2000) and . For hyper-spectral instruments new methods are reported by Clarisse et al (2010) and Gangale et al (2010), which also rely on the characteristic spectral behaviour of volcanic ash and ice that is exploited by Prata (1989b).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other retrieval methods, a lognormal distribution is used with a fixed geometric standard deviation. Clarisse et al (2010) demonstrated an alternate method of optimal estimation using the Infrared Atmospheric Sounding Interferometer (IASI) (Clerbaux et al 2009). This method takes advantage of IASI's high spectral resolution in the range 800-1200 cm −1 (8.3-12.5 μm), but again, an assumption of the ash composition and PSD is needed.…”
Section: Passive Infrared Remote Sensing Of Volcanic Ashmentioning
confidence: 99%